Managing diversity: Reviewing Rule 30 and the implications of the racial vilification laws in the Australian Football League since 1995 - Gorman, Sean; Reeves, K. (Journal of Australian Indigenous Issues, 2012)
This article examines the implications of the Australian Football League’s Rule 30 on vilification in football and society. Considering the views of key industry, government, community, multicultural, Indigenous and academic stakeholders it addresses the themes of community harmony, multiculturalism and reconciliation. The paper evaluates the role of Australian Rules football in changing contemporary attitudes towards vilification and how public policy in this area has been driven by sports-led initiatives such as the AFL Rule 30. It briefly provides an international context for understanding these Australian-led initiatives. ”Racism denies people the fundamental human right to be judged by their character, by what is inside. This is why it is not easy to experience a lifetime of racial abuse, be constantly reminded of it and yet be expected to ignore it”. (The Age 1997: 16).